SOIL FERTILITY OF AGRICULTURE LAND ON PRIVATE-OWNED SECTOR IN VOJVODINA - Sekulić, Petar; Kurjački, Igor; Vasin, Jovica; Šeremešić, Srđan (Economics of Agriculture, 2007)
Scientific basis of the Soil Fertility and Fertilizer Use Control System (in further text, ’the System’) was established in 1980 and it was legislated in 1985. The System encompasses the control of all factors that determine soil fertility and fertilizer action, i.e., how soil affects the growth, development and yield of crops and which measures must be undertaken to ensure high, stable and economic yields and adequate protection of the biosphere. Because of the economic crisis that pestered the country over last 18 years and the recent war devastations, the System was not fully exploited. During 2002-2006, a campaign was launched to conduct soil analyses in the private sector free of charge. The campaign was organized by the Secretariat of Agriculture of the Vojvodina Province and the Institute of Field and Vegetable Crops. The latter is the country’s leading scientific establishment in the field of agriculture. The public response to the campaign fully justifies future intentions to reinstate the System.